Profiles of Self-Efficacy in the Academic Behavior of College Freshman - Martha Ornelas Contreras; Humberto Blanco Vega; Gabriel Gastélum Cuadras; Francisco Muñoz Beltrán (Universidad Autónoma de Baja California, 2013)
The objective of this research was to characterize students who choose to study any of the undergraduate degree programs offered by the Universidad Autónoma de Chihuahua [Autonomous University of Chihuahua] in terms of the perceived self-efficacy of their academic performance. The sample consisted of 1,187 male college students, with an average age of 18.29 (DE=0.76). The approach adopted for the research was quantitative with a survey-type descriptive design. The results show that the profiles of perceived self-efficacy are very similar for students from different fields of study, and that communication-related behaviors represent an area of opportunity for incoming freshmen.